2014
DOI: 10.2174/1570159x11666131120224950
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Regulates Parkin Expression in Mouse Frontal Cortex: Implications in Schizophrenia

Abstract: Stress and glucocorticoid hormones, which are released into the circulation following stressful experiences, have been shown to contribute significantly to the manifestation of various psychiatric illnesses including schizophrenia and depression. Studies in rodents have reported dose and time dependent effects of glucocorticoids on the expression of proteins related to neuroplasticity. However, the mechanism(s) involved in the regulation of proteins by glucocorticoids are not clear. Ubiquitin ligases play impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…The overexpression of RNF122 that we found in persistent ADHD is in agreement with previous studies reporting increased expression levels of E3 ubiquitin ligases in neuropsychiatric disorders 51 , 54 . Given its role in synaptic surface-protein turnover and in the regulation of the number of scaffolding proteins and neurotransmitter receptors, increased ubiquitin ligation and subsequent enhanced protein removal may compromise neuronal functioning 43 , 55 , 56 .…”
Section: Discussionsupporting
confidence: 93%
“…The overexpression of RNF122 that we found in persistent ADHD is in agreement with previous studies reporting increased expression levels of E3 ubiquitin ligases in neuropsychiatric disorders 51 , 54 . Given its role in synaptic surface-protein turnover and in the regulation of the number of scaffolding proteins and neurotransmitter receptors, increased ubiquitin ligation and subsequent enhanced protein removal may compromise neuronal functioning 43 , 55 , 56 .…”
Section: Discussionsupporting
confidence: 93%
“…While the definitive experiment has yet to be conducted, this finding suggests that a stress-induced increase in GC levels would result in an upregulation of parkin expression and accelerate abnormal protein accumulation in PD. That hypothesis is supported by a recent report that mouse cortical neurons in primary culture upregulate parkin mRNA and protein levels following corticosterone treatment ( 343 ).…”
Section: Depression In Parkinson’s Diseasementioning
confidence: 54%
“…It has been reported that hydrocortisone can suppress ER stress 25 and the ATF4 signaling pathway in muscle tissues 26 . Hydrocortisone’s neuroprotective role by acting directly on neuronal cells has not been reported before, although there is a report showing that parkin induction in the frontal cortex by hydrocortisone might be implicated in Schizophrenia disorder 27 . Other parkin inducers including deferasirox, vorinostat, metformin, and clindamycin also elevated ER stress to some extent, consistent with previous reports on these compounds 28 30 .…”
Section: Discussionmentioning
confidence: 98%